AR-glass/carbon-based textile-reinforced concrete elements for detecting water infiltration within cracked zones. (November 2019) - Goldfeld, Yiska; Perry, Gali
The study examines the use of hybrid carbon-based textile-reinforced concrete elements with self-sensing capabilities to quantitatively detect wetting events within cracked zones. The self-sensory structural element combines the advantages of AR-glass and carbon-based textile-reinforced concrete for thin-walled structural elements with those stemming from the electrical properties of reinforced carbon rovings. The article investigates the sensitivity of sensory carbon rovings to distinguish between the magnitudes of various wetting events, which is associated with the severity of the cracking, according to two electrical setups (DC and AC circuits). The sensing concept takes advantage of the continuous configuration of the carbon rovings, which enables direct connection of the roving ends to the data acquisition system, and of the manufacturing process that two carbon rovings are placed adjacent to one another. Therefore, it is assumed that wetting events electrically short-circuit the two adjacent rovings. The sensitivity of the two electrical setups is experimentally investigated and performed on a couple of bared carbon rovings and on a cracked textile-reinforced concrete beam. Test results demonstrate the sensitivity of the sensing capabilities of the carbon rovings to detect and distinguish between the magnitudes of the wetting events and consequently the severity of the cracking.